Seasonal changes in antibiotics, antidepressants/psychiatric drugs, antihistamines and lipid regulators in a wastewater treatment plant - Golovko, Oksana; Kumar, Vimal; Fedorova, Ganna; Randak, Tomas; Grabic, Roman (Chemosphere, 2014)
Seasonal changes in the concentration of 21 pharmaceuticals in a wastewater treatment plant (WWTP) in České Budějovice were investigated over 12months. The target compounds were 10 antibiotics, 4 antidepressants, 3 psychiatric drugs, 2 antihistamines and 2 lipid regulators. 272 Wastewater samples (136 influents and 136 effluents) were collected from March 2011 to February 2012 and analyzed using two-dimensional liquid chromatography coupled with tandem mass spectrometry. All studied pharmaceuticals were frequently detected in both the influent and the effluent wastewater samples, except for meclozine, which was only found in the influent. The mean concentration of pharmaceuticals varied from 0.006μgL(-1) to 1.48μgL(-1) in the influent and from 0.003μgL(-1) to 0.93μgL(-1) in the effluent. The concentration of most pharmaceuticals was higher during winter.
Keywords: Antidepressive Agents; Seasons; Hypolipidemic Agents; Water Pollutants, Chemical; roční období; antibakteriální látky; hypolipidemika; Tandem Mass Spectrometry; chemické látky znečišťující vodu; Removal efficiency; Seasonal variation; odpad tekutý - odstraňování; Wastewater samples; Influent; antihistaminika; Chromatography, High Pressure Liquid; Wastewater; Personal care products; Waste Disposal Facilities; Histamine Antagonists; tandemová hmotnostní spektrometrie; odpadní voda; antidepresiva; vysokoúčinná kapalinová chromatografie; Effluent; Waste Disposal, Fluid; skládková zařízení; Waste Water; Anti-Bacterial Agents; Pharmaceutical Preparations; léčivé přípravky